Detection of Alternative Splice and Gene Duplication by RNA Sequencing in Japanese Flounder, Paralichthys olivaceus. Issue 12 (1st December 2014) - Wang, Wenji; Wang, Jing; You, Feng; Ma, Liman; Yang, Xiao; Gao, Jinning; He, Yan; Qi, Jie; Yu, Haiyang; Wang, Zhigang; Wang, Xubo; Wu, Zhihao; et al.
Abstract: Japanese flounder ( Paralichthys olivaceus ) is one of the economic important fish in China. Sexual dimorphism, especially the different growth rates and body sizes between two sexes, makes this fish a good model to investigate mechanisms responsible for such dimorphism for both fundamental questions in evolution and applied topics in aquaculture. However, the lack of "omics" data has hindered the process. The recent advent of RNA-sequencing technology provides a robust tool to further study characteristics of genomes of nonmodel species. Here, we performed de novo transcriptome sequencing for a double haploid Japanese flounder individual using Illumina sequencing. A single lane of paired-end sequencing produced more than 27 million reads. These reads were assembled into 107, 318 nonredundant transcripts, half of which (51, 563; 48.1%) were annotated by blastx to public protein database. A total of 1051 genes that had potential alternative splicings were detected by Chrysalis implemented in Trinity software. Four of 10 randomly picked genes were verified truly containing alternative splicing by cloning and Sanger sequencing. Notably, using a doubled haploid Japanese flounder individual allow us to analyze gene duplicates. In total, 3940 "single-nucleotide polymorphisms" were detected form 1859 genes, which may have happened gene duplicates. This study lays the foundation for structural and functional genomics studies in Japanese flounder.